Illinois Basin Coal Geology and Roof Control - Marvin B. Thompson (International Conference on Ground Control in Mining, 2010)
"The depositional model for major Illinois Basin coalbeds is well documented and defined on a regional scale. The model was a driving force during past exploration for lower sulfur and thicker coal deposits. The most attractive coal reserves were known to lie along the flanks of contemporaneous sandstone filled stream channels and were overlain by thick silty gray shale roof. At various distances away from the channels, the depositional model transitioned to black shale I limestone roof, sulfur content of the coal bed increased, and the coal bed often thinned. Understanding the character of roof rock types associated with this depositional model is essential to predicting ground control factors on both a regional scale, and on resolving roof control problems at the mine-site. Additionally, horizontal stress and overburden depth are significant factors that impact roof rock quality and ground control in Illinois Basin mines.Determining the character of several rock types, and defining the primary horizontal stress direction were crucial to a recent successful project at New Future Mine, located in southern Illinois. An inclined slope was constructed from the Illinois No. 5 Coalbed up to the Illinois No. 6 Coalbed through strata that ranged from extremely weak ""stackrock"" and a weak underclay unit, to a massive sandstone unit. Engineering geology, operations management, and Jennmar technical services personnel teamedup to select and install roof support for each strata transition. The project was completed with no injuries and no roof falls.INTRODUCTIONAbundant published information concerning coal deposition, geographic distribution, quantity, quality, and mining conditions exists for Illinois Basin coal reserves. The State of Illinois, through its State Geological Survey (ISGS), has provided decades of research, record keeping, and service to the coal industry. Other excellent sources of Illinois Basin coal information include the Indiana Geologiq1l Survey and the Kentucky Geological Survey. Past research by the U.S. Bureau of Mines (USBM) supplemented the work by the geological surveys, especially in the area of horizontal stress and mining hazards. The National Institute for Occupational Safety and Health (NIOSH) continues to produce publications focused on roof control issues common to many coal basins, including the Illinois Basin. Many of the illustrations in this paper originated in ISGS and USBM publications."